On the Structure of Brouwer Homeomorphisms Embeddable in a Flow - Zbigniew Leśniak (Abstract and Applied Analysis)
We present two theorems describing the structure of the set of all regular points and the set of all irregular points for a Brouwer homeomorphism which is embeddable in a flow. The theorems are counterparts of structure theorems proved by Homma and Terasaka. To obtain our results, we use properties of the codivergence relation.